2016
DOI: 10.1038/srep25541
|View full text |Cite
|
Sign up to set email alerts
|

Prokineticin receptor-1 signaling promotes Epicardial to Mesenchymal Transition during heart development

Abstract: The epicardium plays an essential role in coronary artery formation and myocardial development. However, signals controlling the developing epicardium and epicardial-mesenchymal transition (EMT) in the normal and diseased adult heart are studied less rigorously. Here we investigated the role of angiogenic hormone, prokineticin-2 and its receptor PKR1 in the epicardium of developing and adult heart. Genetic ablation of PKR1 in epicardium leads to partial embryonic and postnatal lethality with abnormal heart dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…Mice lacking PKR1 in their epicardial cells displayed a partial embryonic lethality, due to impaired EMT in their hearts. PKR1 signaling promotes the proliferation and EMT of Wt1 + lineage and for their subsequent differentiation into endothelial and vascular SMCs during heart development [18]. However, PKR1 is involved in the reverse process, Mesenchymal to epithelial/epicardial transformation (MET), in the glomerular development of developing kidney, leading to differentiation of kidney progenitors into vasculogenic cells type [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice lacking PKR1 in their epicardial cells displayed a partial embryonic lethality, due to impaired EMT in their hearts. PKR1 signaling promotes the proliferation and EMT of Wt1 + lineage and for their subsequent differentiation into endothelial and vascular SMCs during heart development [18]. However, PKR1 is involved in the reverse process, Mesenchymal to epithelial/epicardial transformation (MET), in the glomerular development of developing kidney, leading to differentiation of kidney progenitors into vasculogenic cells type [41].…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that an angiogenic [15,16] and anorectic hormone [17] prokineticin-2 (PK2), acting via its receptor, PKR1, triggers the EMT of epicardial lineages during cardiogenesis [18], and promotes the vasculogenic differentiation of EPDCs derived from developing mouse hearts [19,20]. PK2/PKR1 signaling prevents the conversion of mouse adipocyte progenitors into adipocytes, and lack of PKR1 in adipose tissue induces obesity [21].…”
Section: Introductionmentioning
confidence: 99%
“…PKR1 signaling in kidney is essential for nephron development during embryogenesis [38]. Recently, it has been shown that mutant mice with targeted PKR1 gene disruptions in nephron progenitors exhibited partial embryonic and postnatal lethality due to hypoplastic kidneys with premature glomeruli and necrotic nephrons.…”
Section: Prokineticin In Renal Development and Functionmentioning
confidence: 99%
“…In developing heart, PKR1 regulates epicardial-mesenchymal transition (EMT) to form epicardial-derived progenitor cell (EPDC) [38]. Genetic ablation of PKR1 in epicardium leads to ventricular hypoplasia and septal defects during embryogenesis.…”
Section: Prokineticin In Cardiovascular Regulationmentioning
confidence: 99%
See 1 more Smart Citation